Cluster randomized controlled trial to assess the effectiveness of a package of community-based interventions on continuum of maternal and newborn healthcare in Sidama, Ethiopia: The SiMaNeH trial protocol - Achamyelesh Gebretsadik; Yemisrach Shiferaw; Hirut Gemeda; Yaliso Yaya (PLoS ONE, 2025)
Background Maternal and newborn mortality and morbidity remain high in low- and middle-income countries such as Ethiopia. Limited access and dropouts from essential continuum of care interventions are critical factors. In Ethiopia, about one in five completes the continuum of essential care through pregnancy, childbirth, and the postnatal period. Evidence is limited on whether packages of interventions involving key community health actors increase the proportion completing essential maternal and newborn healthcare continuum in rural Sidama regional, state, Ethiopia. Objective This study aims to implement and evaluate the cumulative effectiveness of a package of community-based interventions designed to enhance involvement of key community health actors to improve the completion rate of continuum of maternal care and utilization of essential newborn care. Methods Twenty rural kebeles (clusters) in Sidama Regional State, Ethiopia, are randomly allocated to intervention and control arms. A total of 2000 pregnant women, 1000 per arm, will be recruited between 20 th and 26 th week of gestation after intervention. Then the pregnant mothers and their newborn babies will be followed until six weeks postpartum between June 2024 and February 2025. In the intervention arm, mothers and newborns will receive targeted interventions at home and in their community designed to improve the completion rate of recommended maternal and newborn care. Control clusters will receive normal care from the state public health system. Primary outcomes will be the difference in the completion of continuum of essential maternal and rate of use of essential and emergency newborn care and referrals between intervention and control clusters. These outcomes include rates of antenatal care completion, facility deliveries with skilled care, completion of at least four postnatal care contacts, and the overall completion of all the way from first antenatal visit through the postnatal care. Newborn outcomes will be measured through essential newborn care utilization and emergency (danger sign) identification and referrals. Secondary outcomes will include the effect of the intervention on reducing neonatal mortality and stillbirths. Conclusion This trial will implement and evaluate a package of community-based interventions within existing community healthcare infrastructure. The outcome may inform evidence-based community-based decisions to improve the continuum of essential maternal and newborn care. Trial registration The trial is registered at Pan African Clinical Trial Registry: PACTR202402782261294